Extraskeletal Chondroma of the Preauricular Region: A Case Report and Literature Review - Watanabe, Futoshi (Hindawi Publishing Corporation, 2012)
An extraskeletal chondroma is a rare benign cartilaginous tumor that develops in soft tissue. Histologically, it is a lobulated nodule surrounded by a fibrous capsule; the inside consists of mature hyaline cartilage containing a few normal chondrocytes. We present a rare case of extraskeletal chondroma in the preauricular region. A 43-year-old man presented with a 2-cm-diameter right preauricular tumor that had been developing for 1 year. Magnetic resonance imaging showed a solid lobulated tumor in the right preauricular region, which was proximate to the capsule of the right temporomandibular joint (TMJ). This was subsequently resected under general anesthesia. The tumor was not in contact with the TMJ capsule and had not invaded the surrounding tissue, facilitating en bloc excision. Histopathologically, the tumor comprised mainly of hyaline cartilage containing chondrocytes with chondrocytic lacunae and was diagnosed as a chondroma. The postoperative period was uneventful, and there was no evidence of recurrence at the 2-year followup. We describe the clinical characteristics of our case and review the literature, emphasizing the differential diagnosis.